Development and characterization of the thermal behavior of packaged cascode GaN HEMTs. (January 2016) - Chou, Hsin-Ping; Cheng, Stone; Cheng, Chia-Hsiang; Chuang, Chia-Wei
Abstract: This study investigates the heat generation behavior of packaged normally-on multi-finger AlGaN/GaN high electron mobility transistors (HEMTs) that are cascoded with a low-voltage MOSFET (LVMOS) and a SiC Schottky barrier diode (SBD). By foremost carrying out electro-thermal simulation and related thermal measurements with infrared thermography and Raman spectroscopy for basic 5 mm GaN HEMTs, the location of hot spot in operating device can be obtained. Based on the outcome, further packaged cascode GaN HEMT is analyzed. A hybrid integration of the GaN-HEMT, LVMOS, and SiC SBD are assembled on a directly bonded copper (DBC) substrate in the four-pin metal case TO-257 package. The metal plate is used as both the source terminal and heat sink. The analytical results of thermal investigation are confirmed by comparing them with the infrared thermographic measurements and numerical results obtained from a simulation using Ansys Icepak. For a power dissipation of less than 11.8 W, the peak temperature of the GaN HEMTs is 118.7 °C, obtained from thermal measurements.